Stylistic devices in Indian literature and arts: Gargnano del Garda, September 16 - 18, 2010 - Boccali, Giuliano (Acme / Quaderni, 2013)
Literaturangaben
Papers presented at a seminar, Gargnano del Garda, Italy, Sep. 16-18, 2010, and other essays
Incl. abstracts
Includes bibliographical references
Keywords: India -- Languages -- Congresses; Indien; Konferenzschrift -- 2010 -- Gargnano; Stilistik; Kunst; Literatur; Indische Sprachen